Practicing empathy through a virtual exchange course: A study depicting polish and Lebanese students - Ahmad, Manal; Nabhan, Rabih; Khoueiry, Joe; Haddad, Jihad (Edelweiss Applied Science and Technology, 2025)
This study examines the role of empathy in online learning by analyzing the experiences of Polish and Lebanese students enrolled in the Global Understanding (GU) virtual exchange course. While empathy has been widely acknowledged as a critical component of interpersonal and academic interaction, most prior research has examined its development in face-to-face contexts, with limited attention to structured virtual environments. The purpose of this study is to address this gap by investigating whether and how empathy can be cultivated through intercultural dialogue and collaborative online projects. The design follows a case-oriented framework, and a qualitative methodology was adopted, drawing on participant reflections, instructor observations, and project feedback. The approach was intercultural and learner-centered, conducted during five videoconferencing sessions and a joint group project. The findings highlight both emotional and cognitive engagement, expressed in openness, curiosity, and respect toward cultural differences. Emerging themes included academic life, family traditions, religion, and stereotypes, which encouraged reflection on similarities and differences. Instructor reflections confirmed cautious yet meaningful engagement with sensitive issues. In conclusion, the study demonstrates that empathy can be developed in technology-supported contexts. The practical implications suggest that structured virtual exchange fosters empathy, intercultural awareness, and readiness for global citizenship.